Regional differences in the use of technologies in health higher education during the Covid-19 pandemic (Research, Society and Development, 2022)
As a result of the Covid-19 pandemic, many life processes were modified, requiring adaptations in the fields of work, leisure and education. Thus, the objective of this study was to verify the use of Information and Communication Technologies - ICT, by undergraduates, graduate students and teachers, from health courses, in the five regions of Brazil, during this pandemic. Therefore, a quantitative and cross-sectional study approach was adopted, using a questionnaire available on the REDCap platform. For data analysis, the R software and Student's t test were used to assess statistical significance. The study included 1,172 professors and students, 7.5% from the North region, 14.1% from the Northeast region, 5.8% from the Midwest region, 48.5% from the Southeast region and 24.1% from the South region. The analysis of the national variation in the time using ICT, from 2019 to 2020, showed an increase of 21% (p